Puc Museu Project: museological praxis developed at the Pontifical Catholic University of São Paulo (PUC-SP) - Pasqualucci, Luciana (Revista CPC, 2021)
The article presents the PUC Museum Project, which is a museological praxis developed at the Pontifical Catholic University of São Paulo (PUCSP), by its Office of International and Institutional Affairs, since 2017. The theoretical foundations of the reflection are based on the articulation between education and culture and, therefore, university and museum. Approaching the cultural education from the perspective of Theodor Adorno’s critical theory, and the museological practice as an exercise of the museum fact under the inspiration of Waldisa Rússio’s definition of Museology, the argument clearly identifies the relationship between Higher Education curriculum and culture as a possibility of deterritorialization of the classroom, the university, and the museum. Likewise, in understanding education as a subjective appropriation of culture, in accordance with Adorno’s theory, the study proposes an interdisciplinary and institutional integration between university and museum as an alternative for innovation in cognitive, curricular, and cultural practices.